Modern Paradigm: Democratic Skills in a Higher Order Thinking Skills Frame - Guruh Prasetyo; Hermanu Joebagio; Sri Yamtinah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The demand for expertise in technology and rapid service in the modern era has penetrated the field of education. According to Geogi Lozanov in Robinson (2005: 1) in reaching citizens who are sensitive to the development of science and technology and have the ability to interact internationally requires critical thinking skills and democratic attitudes. Critical thinking also requires skills to think about assumptions in asking questions about the concept of democracy that is being discussed before it becomes an option to be developed into a way of living together as a nation. Efforts to reach generations of citizens who have critical thinking skills and have democratic skills are one of the goals of national education, one of them is learning. Besides that, in the effort to reach the generation of democratic citizens in the modern era, high order thinking skills are also needed. This ability to think at a higher level requires someone to apply new information or prior knowledge. The purpose of this study is to describe the concepts of democratic skills in the HOTS stage in the modern era. The method in this study uses a descriptive qualitative approach. The concepts of democratic skills in the HOTS frame are civic skills, intellectual skills, and participation skills. Through this research, HOTS is expected to strengthen democratic skills in the modern era.